Comparative pharmacokinetics and tissue distribution of cryptotanshinone, tanshinone IIA, dihydrotanshinone I, and tanshinone I after oral administration of pure tanshinones and liposoluble extract of Salvia miltiorrhiza to rats. (22nd January 2020) - Wang, Daifei; Yu, Weibang; Cao, Lin; Xu, Chuncao; Tan, Guoyao; Zhao, Zhongxiang; Huang, Min; Jin, Jing
Abstract: Salvia miltiorrhiza is one of the most commonly used traditional Chinese medicines in the treatment of cardiovascular and cerebrovascular diseases. Cryptotanshinone (CTS), tanshinone IIA (Tan IIA), dihydrotanshinone I (diTan I), and tanshinone I (Tan I) are the main active compounds in the liposoluble extract of Salvia miltiorrhiza. The differences in the pharmacokinetic and tissue distribution behaviors of the four tanshinones after oral administration of the liposoluble extract of Salvia miltiorrhiza and pure compounds are not clear. This study aims to compare the pharmacokinetics and tissue distribution of the four tanshinones after oral administration of pure tanshinone monomers and the liposoluble extract of Salvia miltiorrhiza. An ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) analysis method was developed for the determination of the four tanshinones. The results showed that the AUC and Cmax of tanshinones in rats receiving the extract of Salvia miltiorrhiza were significantly increased compared with those receiving the pure tanshinones. In the tissue distribution experiments, the AUC of the four tanshinones in the extract was much greater than the AUC of the monomers in the lung, heart, kidney, liver, and brain, and the coexisting constituents particularly promoted the distribution of tanshinones into tissues that the drug cannot sufficiently penetrate. These findings suggested that the coexisting constituents in the liposoluble extract of Salvia miltiorrhiza play an important role in the alteration of plasma concentration and tissue distribution of the four tanshinones. Understanding these differences could be of significance for the development and application of Salvia miltiorrhiza extract and tanshinone components.